2020
DOI: 10.3390/molecules25204785
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Biomimetically Mineralized Composite Materials in Human Hard Tissue Repair

Abstract: Chitosan is a natural, biodegradable cationic polysaccharide, which has a similar chemical structure and similar biological behaviors to the components of the extracellular matrix in the biomineralization process of teeth or bone. Its excellent biocompatibility, biodegradability, and polyelectrolyte action make it a suitable organic template, which, combined with biomimetic mineralization technology, can be used to develop organic-inorganic composite materials for hard tissue repair. In recent years, various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 124 publications
(161 reference statements)
0
25
0
Order By: Relevance
“…Chitosan has been considered a versatile polymer for tissue engineering applications due to its biocompatibility, controllable biodegradability, and the capability of being processed into different architectures (Hu et al 2020; Tang et al 2020). Amino (-NH 2 ) and hydroxyl groups (-OH) are effective centers for complexing with metal ions and are directly involved in the metal-chitosan coordination process (Hu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan has been considered a versatile polymer for tissue engineering applications due to its biocompatibility, controllable biodegradability, and the capability of being processed into different architectures (Hu et al 2020; Tang et al 2020). Amino (-NH 2 ) and hydroxyl groups (-OH) are effective centers for complexing with metal ions and are directly involved in the metal-chitosan coordination process (Hu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has attracted attention for dentin tissue regeneration due to glycosaminoglycan-like polymeric chains, which favor pulp cells interaction, along with proved biocompatibility, biodegradability into nontoxic components, protein affinity, and hemostatic and antimicrobial potential (Hu et al 2020; Tang et al 2020). Previous in vivo studies have already demonstrated that chitosan scaffolds might be useful for in situ tissue engineering of dentin due to adequate absence of cell/tissue toxicity, promoting cell mobilization and interaction, ultimately with odontoblastic differentiation and mineralized tissue deposition in absence of inflammatory reaction on surrounding pulp tissue (Li et al 2014; Machado et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have tried and are still trying to overwhelm the shortfalls. The most hopeful ones are those that combine chitosan-based formulations and synthetic inorganic biomaterial similar to the calcified phase of natural bone [42].…”
Section: Chitosan In Bone Tissues Therapymentioning
confidence: 99%
“…HA is one of the most used biomaterials for bone regeneration because its inorganic component is similar to natural apatite, the mineral that constitutes bone matrix and provides rigidity to bone [ 3 , 4 ]. It is biocompatible, minimally inflammatory, osteoconductive, osteoinductive, and biodegradable [ 5 , 6 ]. Moreover, HA can be prepared both by synthetic and natural sources via easy fabrication strategies, which makes it an attractive grafting material [ 7 ].…”
Section: Introductionmentioning
confidence: 99%